2012
DOI: 10.5114/aoms.2012.31135
|View full text |Cite
|
Sign up to set email alerts
|

State of the art paper Deep brain stimulation for refractory epilepsy

Abstract: Deep brain stimulation (DBS) is a method of treatment utilized to control medically refractory epilepsy (RE). Patients with medically refractory epilepsy who do not achieve satisfactory control of seizures with pharmacological treatment or surgical resection of the epileptic focus and those who do not qualify for surgery could benefit from DBS. The most frequently used stereotactic targets for DBS are the anterior thalamic nucleus, subthalamic nucleus, central-medial thalamic nucleus, hippocampus, amygdala and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 84 publications
0
18
0
Order By: Relevance
“…Physical side effects include intracranial hemorrhage, which has a prevalence of 0.4-1.3% and irreversible brain damage, which has a prevalence of 0.8% (89). Furthermore, studies in patients who have undergone DBS have found that the prevalence of infection, epileptic seizure and cutaneous complications are 0.7, 1.5 and 25%, respectively (87,90,91).…”
Section: The Side-effect Of Dbsmentioning
confidence: 99%
“…Physical side effects include intracranial hemorrhage, which has a prevalence of 0.4-1.3% and irreversible brain damage, which has a prevalence of 0.8% (89). Furthermore, studies in patients who have undergone DBS have found that the prevalence of infection, epileptic seizure and cutaneous complications are 0.7, 1.5 and 25%, respectively (87,90,91).…”
Section: The Side-effect Of Dbsmentioning
confidence: 99%
“…21,22,33 The dorsolateral sensorimotor region of the STN in Parkinson's disease is the generally accepted target for DBS treatment of motor symptoms, such as tremor and bradykinesia. 11,13,15,28,33,42,44,56 STN stimulation has also been explored as an option to treat refractory epilepsy and obsessive-compulsive disorder. 11,13,15,28,56 Precise and thorough identification of the 3D anatomy of the STN and related structures is a prerequisite for all of these DBS procedures.…”
Section: Discussionmentioning
confidence: 99%
“…11,13,15,28,33,42,44,56 STN stimulation has also been explored as an option to treat refractory epilepsy and obsessive-compulsive disorder. 11,13,15,28,56 Precise and thorough identification of the 3D anatomy of the STN and related structures is a prerequisite for all of these DBS procedures. Safe and effective DBS procedures targeting the STN also depend on a thorough understanding of the 3D anatomy of the region, which is critical for proper assessment of both outcomes and adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…Other brain structures have been tried as well to control seizures; for examples, the centromedian nucleus of thalamus, the subthalamic nucleus, the substantia nigra reticulata, the caudate nucleus, the cerebellum, the posterior hypothalamus, and the caudal zona incerta [43]. Subthalamic nucleus, cerebellum, and trigeminal nerve stimulations have been considered as possible targets for intractable epilepsy especially for generalized epilepsy patients.…”
Section: Targets For Neurostimulationmentioning
confidence: 99%